Resource management for increased wheat productivity: Achievements and challenges - Sharma, R K; Chhokar, R S; Gill, S C; Singh, S S (Indian Farming, 2015)
Efficient external inputs usage coupled with environmental friendly natural resource management is the key to farm profitability and sustainability as well as for long term national food and nutritional security. Laser land leveling is a must to get the maximum benefit of tillage technologies like zero tillage, bed planting, rotary tillage and seeding into surface retained residue with minimum soil disturbance. Integrated nutrient management along with balanced ferilisation practices needs to be followed to overcome the multiple nutrient deficiencies being encountered across the country. In addition, herbicide resistance in weeds, especially Phalaris minor, is a threat to wheat productivity in northern plains and we must focus on developing strategies to address this issue. Intercropping wheat with sugarcane and relay cropping wheat with cotton can help increase the productivity of the system as well as area and production of wheat. Introducing legume crop in cerealcereal rice-wheat monocropping can help enhance the productivity and sustainability of the natural resources.